Numerical exploration of heat transfer in a heat exchanger tube with cone shape inserts and Al2O3 and CuO nanofluids. (2020) - Karuppasamy, M.; Saravanan, R.; Chandrasekaran, M.; Muthuraman, V.
Abstract: Offering the small disturbance in the flow without affecting the pumping force is one of the passive techniques of augmenting the heat transfer in the double tube heat exchanger (DTHE). The flow disturbance is offered by the inserts like twisted tape with different ration of twist to make the swirl in the flow in the tube. The properties of fluid medium also a contributing more in the heat transfer. Objective of this research work is to augment the heat transfer rate in DTHE with help of cone shape inserts and Nanofluids. The cone shape insert create turbulence in the flow and the nano sized (<100 nm) powder which suspended on the fluid increase the thermal conductivity of the fluid. The Al2 O3 and CuO Nano particles 1% of volume fraction, suspended in the water to improve the heat transfer rate in the effective of are used for this analysis and 3D model of cone and plain tube generated in solid works software and CFD Analysis done in ANSYS-Fluent Software, in this results Al2 O3 Nano particles get the higher heat transfer rate in with and without cone inserted.